Quality assessment and umbrella review of systematic reviews about dance for people with Parkinson's disease. - Camila Pinto; Rafaela Simon Myra; Alexandre Severo do Pinho; Francisca Pereira; Guido Orgs; Aline Souza Pagnussat (PLoS ONE, 2024)
Objective(s) To determine (1) the quality of systematic reviews about dance-based intervention in individuals with Parkinson's disease (PD) and (2) standard evidence for dance-based intervention efficacy based on the categories of The International Classification of Functioning, Disability, and Health (ICF) from the World Health Organization's (WHO). Methods The data source included MEDLINE, PUBMED, Embase, Scopus, CENTRAL (Cochrane Library), CINAHL, PEDro, SPORTDiscus, APA PsycNet (APA PsycINFO), LILACS, SciELO, and AMED. Pairs of independent reviewers screened titles, abstracts, and full texts of eligible studies by using the software Covidence. Criteria included: systematic review designs; individuals with PD; dance-based interventions aimed to change critical PD symptoms matched to IFC domains (body functions, activities, and participation). Independent reviewers extracted information regarding the characteristics of all systematic reviews included and appraised quality using A MeaSurement Tool to Assess Systematic Reviews (AMSTAR 2). Randomized controlled trials and their risk of bias were identified within each review and were used to perform an updated pairwise meta-analysis. Results Of the 571 manuscripts screened, 55 reviews met the inclusion criteria. The overall confidence in the results of 38 reviews (69%) was rated as 'critically low,' nine (9%) as 'low,' one (2%) as 'moderate,' while seven of 55 reviews (13%) were rated as 'high'. Dance associated with pharmacological usual care is better than pharmacological usual care alone for essential components of ICF, such as motor symptoms severity (body function), depressive symptoms (body function), balance (body function and activity), and functional mobility (activity), but not for gait distance (activity) and quality of life (participation). Dance is also superior to multimodal exercise to improve balance. Conclusions Clinicians and people with PD can refer to this paper for a summary of high-quality reviews and the overall evidence supporting dance as an adjunct rehabilitation. This umbrella review not only underscores the therapeutic potential of dance but also reinforces the use of arts-based approaches into healthcare practices for people with neurological conditions.